Analysis of Pavement Condition Using The International Roughness Index (IRI) Method With The Roadroid Application on The Genengan–Lembeyan Road Section In Magetan District - Adi Purwanto; Hanie Teki Tjendani; Budi Witjaksana (Journal of Social Research, 2025)
The Genengan–Lembeyan road in Magetan Regency serves as a vital transportation route, connecting Magetan and Ponorogo Regencies. As a primary collector road, it facilitates the distribution of goods and community mobility but experiences significant surface deterioration due to high traffic volumes and heavy vehicle loads. This study evaluates the pavement condition using the International Roughness Index (IRI) method, supported by the Roadroid application, a smartphone-based tool for assessing road unevenness. The research identifies an average IRI value of 4.24, which suggests that the overall road condition is moderate to good. However, critical segments, particularly between STA 5+000 and STA 8+660, exhibit moderate to severe damage, including cracks, potholes, and surface deformations, necessitating immediate repair. The estimated repair costs, calculated using the Bina Marga 2024 guidelines, amount to IDR 4,069,031,000. This study emphasizes the effectiveness of the Roadroid application in providing accurate, real-time road condition data, offering a cost-efficient and practical alternative to conventional methods. The findings underline the importance of timely maintenance to prevent further deterioration, enhance road safety, and sustain transportation efficiency. Furthermore, the study advocates for regular evaluations using innovative tools like Roadroid and improved drainage systems to mitigate damage caused by environmental factors. The insights from this research contribute to better infrastructure management in Magetan Regency, demonstrating that integrating modern technology can optimize road maintenance planning and execution while supporting economic growth through reliable transportation networks.